BAHASA INDONESIA: MATA KULIAH PENGEMBANGAN KEPRIBADIAN DI PERGURUAN TINGGI - Hilda Hilaliyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Abstract: Having Indonesian Language subject as a means of communication concurrently with Mata kuliah Pengembangan Kepribadian (MPK) or Personality Development course at the university level aims to develop students’ competences primarily in scientific writing competence including psychomotor, affective, and cognitive skills. These students are capable of growing as individuals possessing a highly developed intellect, distinctive mental and moral qualities, and ability to use their imagination and creative ideas in their field of interest. The vision of MPK is becoming a reference for values in cultivating Indonesian students into being. Along with this vision, the MPK has a mission to accomplish its vision into reality that is helping Indonesian students at the university level to place their mental and moral qualities on solid footing with the intention that a consistency in religious and cultural values is possible to be accomplished. It also goes hand in hand with the spirit of nationality in action by utilizing these skills to develop science, arts, and technology. Therefore, it is necessary to offer Indonesian Language subject as a fresh guided course namely Mata kuliah Pengembangan Kepribadian bahasa Indonesia at the university level.Keywords: Indonesian language., personality development., higher education